The toxins of vertically transmitted Spiroplasma - Moore, Logan D.; Ballinger, Matthew J. (Frontiers in Microbiology, 2023)
Vertically transmitted (VT) microbial symbionts play a vital role in the evolution of their insect hosts. A longstanding question in symbiont research is what genes help promote long-term stability of vertically transmitted lifestyles. Symbiont success in insect hosts is due in part to expression of beneficial or manipulative phenotypes that favor symbiont persistence in host populations. In Spiroplasma, these phenotypes have been linked to toxin and virulence domains among a few related strains. However, these domains also appear frequently in phylogenetically distant Spiroplasma, and little is known about their distribution across the Spiroplasma genus. In this study, we present the complete genome sequence of the Spiroplasma symbiont of Drosophila atripex, a non-manipulating member of the Ixodetis clade of Spiroplasma, for which genomic data are still limited. We perform a genus-wide comparative analysis of toxin domains implicated in defensive and reproductive phenotypes. From 12 VT and 31 non-VT Spiroplasma genomes, ribosome-inactivating proteins (RIPs), OTU-like cysteine proteases (OTUs), ankyrins and ETX/MTX2 domains show high propensity for VT Spiroplasma compared to non-VT Spiroplasma. Specifically, OTU and ankyrin domains can be found only in VT-Spiroplasma, and RIP domains are found in all VT Spiroplasma and three non-VT Spiroplasma. These domains are frequently associated with Spiroplasma plasmids, suggesting a possible mechanism for dispersal and maintenance among heritable strains. Searching insect genome assemblies available on public databases uncovered uncharacterized Spiroplasma genomes from which we identified several spaid-like genes encoding RIP, OTU, and ankyrin domains, suggesting functional interactions among those domain types. Our results suggest a conserved core of symbiont domains play an important role in the evolution and persistence of VT Spiroplasma in insects.